(untitled) (International Journal of Physiotherapy, 2015)
Background: Although exercising is common among the multidisciplinary approach, but its analgesic effect is still controversial. The purpose of this study was to evaluate the analgesic effect of an exercise program through a booklet for people with chronic non-specific lower back pain, under the direction of a physiotherapist or as an entirely self-directed program. Methods: A prospective and randomized study was done in 44 patients, with pain intensity greater than 3 by VAS. Patients in G1 received a booklet with the exercise program and once a week they had a physiotherapist’s guidance while performing them at the pain care center, while patients in G2 received just the booklet and once a week they went to the pain care center to answer some questionaries. All patients were expected to perform the exercises once a day at home. There were evaluated pain intensity and quality of life before the treatment, after 6 and then 12 weeks. Acetaminophen could be used as necessary. Results: Pain intensity was lower in G1 than in G2, and there was a significant reduction in pain intensity in G1 but not in G2. G1 patients needed less acetaminophen than the patients in G2. Quality of life was higher in G1 than in G2. Conclusions: the patients showed a better outcome (pain intensity, quality of life, and less acetaminophen intake) when the stretching and strengthening exercise program was performed under the direction of a physiotherapist, compared to the patients who had an entirely self-directed exercise program for chronic non-specific lower back pain.